Improved methods for biomarker analysis of the big five mycotoxins enables reliable exposure characterization in a population of childbearing age women in Rwanda - Collins, Stephanie L.; Walsh, Jacob P.; Renaud, Justin B.; McMillan, Amy; Rulisa, Stephen; Miller, J. David; Reid, Gregor; Sumarah, Mark W. (Food and chemical toxicology, 2021)
Of the five agriculturally important mycotoxins, AFB1, FB1, DON, ZEA and OTA, a well-characterized biomarker of exposure in blood is only available for aflatoxin. Working with a population of 139 women of childbearing age in Rwanda, we undertook a comprehensive assessment of their dietary mycotoxin exposure. Using high-resolution LC-MS/MS with stable isotope dilution analysis, the albumin-aflatoxin adduct was quantitated in plasma. Similarly, AFM1, AFB1, AFG1, FB1 and B2, OTA, zearalenone, α-zearalenol, deoxynivalenol, deoxynivalenol-15-glucuronide and deoxynivalenol-3-glucuronide were quantitated in urine. AFB1-Lys was detected in plasma from 81% of the women, indicative of exposures 1–2 orders of magnitude above current guidance. Zearalenone and/or α-zearalenol were detected in the urine of 61% of the women, the majority of whom had estimated exposures 2–5 times the PMTDI, with one third more than an order of magnitude above. Urinary deoxynivalenol or the two glucuronide conjugates were found in 77% of the participants. Of these, 60% were below the PMTDI, 28% were twice and 12% were >10x the PMTDI. Fumonisin B1 (30%) and ochratoxin A (71%) were also detected in urine. Exposures observed in these Rwandan women raise serious food safety concerns and highlight the need for authorities to help manage multiple mycotoxins in their diet. •Multi-mycotoxin exposure characterization in Rwandan women.•Exposures were observed for multiple mycotoxins above tolerable daily intake limits.•Mycotoxin exposure in Rwandan women was higher during pregnancy.